2007
DOI: 10.2166/wst.2007.053
|View full text |Cite
|
Sign up to set email alerts
|

Relationship between the electric conductivity and phosphorus concentration variations in an enhanced biological nutrient removal process

Abstract: Phosphorus release and uptake in a sequencing batch reactor were monitored by the simple online measurements of electric conductivity (EC) and oxidation-reduction potential (ORP), and the result was verified by the measurement of phosphate concentration changes. The influence of nitrate ion presence on the phosphorus removal was evaluated by a jar test operated in the cyclic anaerobic (anoxic)-aerobic condition. The relationships of EC, ORP and metal species with phosphorus concentrations were investigated. Un… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 4 publications
0
7
0
Order By: Relevance
“…The use of the conductivity sensor was efficient for rapid monitoring of the anaerobic metabolic tests conducted in the off‐line batch cell under standardized medium composition and pH and temperature conditions. As previously explained, conductivity profiles nevertheless comprise the contribution of all ions present in the medium, and might be altered by the evolutions of nitrate in SBRs operated for full BNR (Kim et al, ; Villez et al, ). Further investigations are required toward a possible transposition of this method for the in situ assessment of the active PAO fractions during the anaerobic phase of these SBRs.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The use of the conductivity sensor was efficient for rapid monitoring of the anaerobic metabolic tests conducted in the off‐line batch cell under standardized medium composition and pH and temperature conditions. As previously explained, conductivity profiles nevertheless comprise the contribution of all ions present in the medium, and might be altered by the evolutions of nitrate in SBRs operated for full BNR (Kim et al, ; Villez et al, ). Further investigations are required toward a possible transposition of this method for the in situ assessment of the active PAO fractions during the anaerobic phase of these SBRs.…”
Section: Discussionmentioning
confidence: 99%
“…including both phosphorus and nitrogen removal (Villez et al, ). Although correlations between conductivity and soluble phosphate concentrations become insignificant in the presence of nitrate in such systems, conductivity has nevertheless been shown to display a direct positive correlation with Pi‐release during strict anaerobic batch phases (Kim et al, ).…”
Section: Introductionmentioning
confidence: 99%
“…According to [28] the level of EC is categorized as normal. [29] reported that under anaerobic condition EC has a tendency of showing positive correlation with phosphorus concentrations. The texture of the soil was sand clay.…”
Section: Physico-chemical Properties Of the Soil Used In The Incubation Experimentsmentioning
confidence: 98%
“…Temperature was controlled at 20 ± 1°C. Conductivity in the bulk liquid was used to follow phosphate release and uptake profiles as described in Kim et al (2007). The on-line profiles were used to verify steady operation of the reactor.…”
Section: Reactor Operationmentioning
confidence: 99%